The Child's Right to Know Versus the Parents’ Right Not to Tell: The Attitudes of Couples Undergoing Fertility Treatments Towards Identity-Release Gamete Donation - DR Rocha; RMM Melamed; DPAF Braga; AS Setti; JrA Iaconelli; E Borges (JRI, 2023)
Background: In Brazil, donor anonymity is mandatory; however, the tendency of Brazilians towards the practice is unknown. In this study, an attempt was made to investigate whether couples undergoing assisted reproductive technology (ART) have a different perception of anonymous versus identity-release gamete donation than a target population in Brazil. Methods: This cross-sectional study was performed from September 1, 2020 to December 15, 2020. For that purpose, surveys through online platforms were conducted, including either patients undergoing ART (ART-group, n=400) or subjects interested in the theme (interested-group, n=100) randomized by age at a 1:4 ratio. The survey collected information on the participants’ attitudes towards anonymity of gamete donors, and answers were compared between the groups. Results: Most participants stated that the relationship between children and their parents would be affected by the child's knowledge of the origin of its conception. Most participants in the ART-group believed that the gamete donor’s identity should not be revealed to the child, while only half of the interested-group stated the same. Most of the participants stated that "the donor's identity should be revealed if the child questions its biological origin". "From birth" was the second most common response, while "when the child turns 18 years old" and "sometime during teenage years" were less common answers. Conclusion: The attitudes of ART patients about anonymity are conservative, with most participants believing that family relationships may be affected if the child is aware of the origin of his/her conception. These patients also believe that the identity of the gamete donor should not be revealed to the child.